Numerical Study of Performance of Centrifugal Pump for Handling Ash Slurry - Kumar, Ashutosh (My University, 2008)
Centrifugal pumps are used extensively for hydraulic transportation of solids over short to medium distance through pipelines where the requirements of head and discharge are moderate. A centrifugal pump designed to handle solid-liquid mixtures is normally single stage, end suction type having radial and mixed flow configuration to facilitate the motion of solid particles. Some of the special features of the centrifugal slurry pumps are larger flow passages to accommodate solid particles, robust impeller with lesser number of vanes, special seals and proper material of construction to ensure longer life. These have to be operated with relatively wide clearance at impeller-casing contacts to minimize choking and localized wear. These modifications increase the hydraulic losses in the pump and deteriorate the pump performance. During the design of pump handling abrasive slurries, the requirement of longer life and reliability have to be balanced by the constraint of high initial cost and efficiency. The present works is concerned with the evaluation of the performance and wear characteristics of a centrifugal slurry pump. To achieve the above objectives the performance of the centrifugal slurry pump has been evaluated at different speed with clear water and with ash slurry at different solid concentration (by weight) with bed ash as solid material whose specific gravity is 2.65. At all the speed, the head developed and efficiency of the pump is found to reduce with increase in solid concentrations. The power input to the pump is also found to increase almost linearly with increase in specific gravity of slurry. The wear characteristics of centrifugal slurry pumps are much influenced by various particle parameters like particle size, concentration and flow velocity of slurry etc. For this purpose design code has been written in C++. Thereafter, output of the program has been used for modeling of impeller and volute casing of pump and then numerical analysis is done on it to find out the wear rate for slurries of different concentration and solid particle size on the volute casing of the centrifugal pump for handling ash slurry.
Keywords: centrifugal pump,performance characteristics,wear